The Effect of Financial Compensation on Employee Performance at Pt. Bank Btpn Sungguminasa Branch, Gowa Regency - Eka Pradila Putra (Junal Ilmu Manajemen, 2022)
Financial competence is one of several factors that can affect the level of employee performance. Compensation is an addition to the basic salary that employees do not expect, but only part of it can be given, only they have certain achievements or certain skills and do not disobey if asked to complete as soon as possible, such as reports or receipts that must be reported. This research was conducted by using a simple linear regression analysis tool, F test and t test to analyze the close relationship of 1 variable. The purpose of this study was to determine the effect of financial competence on the performance of employees at PT. Bank btpn sungguminasa gowa district.